A monograph of the Afrotropical Cassidinae (Coleoptera: Chrysomelidae). Part 5. Revision of the genus Aethiopocassis Spaeth - Borowiec, Lech (Zootaxa, 2018)
The genus Aethiopocassis Spaeth, 1922 is revised and 31 species are recognized as valid, all distributed in Sub-Saharan Africa. Seven species are described as new: Aethiopocassis angulicollis sp. nov. (Tanzania), Aethiopocassis dewittei sp. nov. (Democratic Republic of Congo), Aethiopocassis garambana sp. nov. (Democratic Republic of Congo), Aethiopocassis guineensis sp. nov. (Guinea), Aethiopocassis huilaensis sp. nov. (Angola), Aethiopocassis longidoana sp. nov. (Tanzania), and Aethiopocassis transvaalensis sp. nov. (Republic of South Africa). The following new synonyms are proposed: Aethiopocassis fugax (Spaeth, 1906) = Cassida (Aethiopocassis) scita Spaeth, 1924 syn. nov.; Aethiopocassis gallarum (Spaeth, 1906) = Cassida deplanata Spaeth, 1906 syn. nov. = Cassida sjoestedti Spaeth, 1906 syn. nov. = Cassida (Aethiopocassis) burensis Spaeth, 1924 syn. nov.; Aethiopocassis pauli (Weise, 1898) = Cassida pauli var. deleta Weise, 1899 syn. nov. = Cassida (Aethiopocassis) alluaudi Spaeth, 1924 syn. nov.; Aethiopocassis silphoides (Spaeth, 1906) = Cassida (Aethiopocassis) silphoides ssp. katangana Spaeth, 1933 syn. nov.; Aethiopocassis suspiciosa (Weise, 1903) = Cassida suspiciosa var. connexa Weise, 1906 syn. nov. = Cassida suspiciosa ssp. picturata Spaeth, 1934 syn. nov. = Cassida manubialis Spaeth, 1906 syn. nov., = Cassida decipiens Spaeth, 1906 syn. nov. = Cassida (Aethiopocassis) maynei Spaeth, 1933 syn. nov. = Aethiopocassis suspiciosa ssp. flavofemorata Spaeth, 1934 syn. nov. = Aethiopocassis maynei ssp. biramosa Spaeth, 1934 syn. nov. Colour photos, including intraspecific variablity, a key to species and maps of distribution are given.